The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10517-017-3637-x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Xenon in Rat Model of Inflammatory Pain

Abstract: The analgesic effects of inert gas xenon were examined on rats. The formalin model of inflammatory pain, tail-flick test, and hot-plate test revealed the antinociceptive effects of subanesthetizing doses of inhalation anesthetic xenon. Inhalation of 50/50 xenon/oxygen mixture moderated the nociceptive responses during acute and tonic phases of inflammatory pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“… Koziakova et al (2019) demonstrated that the neuroprotective effect of xenon may be mediated by inhibition of the N -methyl-d-aspartate receptor at the glycine site. Kukushkin et al (2017) demonstrated that in simulated models of two kinds of physiological pain (formalin-induced acute pain and tonic pain), the TWL of pain behavior in rats was relieved after 15 min after inhalation of 50/50% xenon/oxygen for 30 min. The analgesic effect of PWMT was stable within 60 min ( Kukushkin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Koziakova et al (2019) demonstrated that the neuroprotective effect of xenon may be mediated by inhibition of the N -methyl-d-aspartate receptor at the glycine site. Kukushkin et al (2017) demonstrated that in simulated models of two kinds of physiological pain (formalin-induced acute pain and tonic pain), the TWL of pain behavior in rats was relieved after 15 min after inhalation of 50/50% xenon/oxygen for 30 min. The analgesic effect of PWMT was stable within 60 min ( Kukushkin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“… Kukushkin et al (2017) demonstrated that in simulated models of two kinds of physiological pain (formalin-induced acute pain and tonic pain), the TWL of pain behavior in rats was relieved after 15 min after inhalation of 50/50% xenon/oxygen for 30 min. The analgesic effect of PWMT was stable within 60 min ( Kukushkin et al, 2017 ). Where xenon plays a major role in this sensitization is the long-lasting depolarization of glutamate and neurokinin exerted on nociceptive dorsal horn neurons ( Kukushkin & Igonkina, 2014 ).…”
Section: Discussionmentioning
confidence: 99%